Seismic safety assessment of historical structures using updated numerical models: The case of Mallorca cathedral in Spain. (April 2017) - Elyamani, Ahmed; Roca, Pere; Caselles, Oriol; Clapes, Jaime
Abstract: The paper presents an integrated approach aimed at assessing the seismic safety of Mallorca cathedral. This cathedral is an extraordinary historical construction dating back to the middle-ages. The experimental modal parameters of the cathedral were identified using Ambient Vibration Testing (AVT). The cathedral numerical model was updated using the identified modal parameters. This updated model was then used to study the seismic response of the cathedral using non-linear static (pushover) analysis. A sensitively analysis was carried out to reveal the dependency of the seismic capacity on the input materials properties. To assess the seismic performance and the safety of the cathedral, the N2 method was employed. It was found that the cathedral is safe when subjected to the earthquakes expected in Mallorca Island. Highlights: Ambient Vibration Testing of a large historical structure. System identification using four different techniques. Successful manual model updating and good matching between experimental and numerical modes. Nonlinear static analysis of a large cathedral followed by sensitivity analysis. Employment of N2 method to assess the seismic safety of the cathedral.